The Role of Klotho G395A Gene Polymorphism in Atherosclerotic Cardiovascular Disease and Mortality Risk Scores in Non-dialysis Chronic Kidney Disease - Hendri Susilo; Budi Susetyo Pikir; Mochammad Thaha; Mochamad Yusuf Alsagaff; Satriyo Dwi Suryantoro; Citrawati Dyah Kencono Wungu; David Setyo Budi; Laurentius Andre; Cennikon Pakpahan (The Prodia Education and Research Institute (PERI), 2022)
BACKGROUND: Cardiovascular disease (CVD) is the leading cause of death in patients with chronic kidney disease (CKD). Klotho expression was reduced in patients with CKD, leading to vascular calcification, endothelial dysfunction, and atherosclerosis. We investigated the role of the klotho G395A gene polymorphism and plasma klotho level in the ten-year risk of atherosclerotic cardiovascular disease (ASCVD) and CVD mortality in CKD patients.METHODS: We used the PCR-CTPP assay method to genotype klotho G395A single nucleotide polymorphism (SNP) in 72 non-dialysis CKD patients. The klotho level was determined using the enzyme-linked immunoassay (ELISA) method. Path analysis was used to determine the relationship between the klotho G395A SNP, plasma klotho level, ASCVD risk score, and CVD mortality risk score.RESULTS: Our results showed that the GA genotype had lower plasma klotho levels than the GG genotype (path coefficient=-0.185, p=0.000). There was a significant negative correlation between plasma klotho level and the ASCVD risk score (r=-0.243, p=0.040), but no significant correlation was found between plasma klotho level and the CVD mortality risk score (r=-0.145, p=0.225). Path analysis showed that plasma klotho level had a significant negative direct effect on ASCVD risk score (path coefficient=-0.272, p=0.000) and an indirect effect on CVD mortality risk score (path coefficient=0.187, p=0.005).CONCLUSION: Klotho G395A SNP might reduce lower plasma klotho levels, which increased ASCVD and CVD mortality risk scores in non-dialysis CKD patients. However, other risk factors such as age, CKD stages, hypertension, and smoking should be taken into consideration. Therefore, large-scale genetic association studies with adjusted variables could be conducted in various ethnic groups for a more robust result.KEYWORDS: klotho, single nucleotide polymorphism, cardiovascular disease, chronic kidney disease